IMPACT THAT SEQUELIZES BRINGS TO THE DEVELOPMENT OF AN API BUILT IN NODE.JS WITH EXPRESS.JS - Barsoti, Nathan; Gibertoni, Daniela (Revista Interface Tecnológica, 2020)
As the software development Market has been considerably increasing its demand, aiming to solve and optimize problems, ensuring product quality and customer satisfaction, increasingly shorter deadlines and delivery times are required. Because of so much competition for improvements and fast deliveries, mechanisms and facilitators emerge to increase the productivity in codifying and to facilitate the maintainability and confidentiality through frameworks. This article addresses, through experimental and exploratory bibliographical research, how the use of Sequelize, an ORM (Object-Relational Mapper), impacts on the development of an API (server side) built in Node.js with Express.js, from which it was developed a web system for a range of dentists located in the Itápolis/SP region, with the purpose of identifying the main vantages in using Sequelize in this case study. As main results, there are the search for maintaining and reliability of the code, and for optimization in the process of API creation, through Node.js, Express.js and Sequelize functionalities.